Gout Augments the Risk of Cardiovascular Disease in Patients With Psoriasis: A Population-Based Cohort Study - Chen, Zhiyong; Xu, Yiwen; Chen, Miao; Cui, Ran; Wang, Yu-Hsun; Dai, Sheng-Ming; Wei, James Cheng-Chung (Frontiers in Immunology, 2021)
Objective: Patients with psoriasis (PsO) have a high frequency of concomitant gout and increased risk of cardiovascular diseases (CVD). We aimed to estimate the synergistic impact of gout on the risk of CVD in patients with PsO. Methods: A population-based cohort of patients registered in the National Health Insurance Research Database of Taiwan between 2000 and 2013 was stratified according to the presence of PsO and gout. Propensity score analysis was used to match age and gender at a ratio of 1:4. Cox proportional hazard models and subgroup analyses were used to estimate the hazard ratios (HRs) for CVD adjusted for traditional risk factors. The Kaplan–Meier method was used to plot the cumulative incidence curves. Results: Patients with combined PsO and gout (n = 97), PsO alone (n = 388), gout alone (matched, n = 388) and matched controls (n = 388) were identified. Compared with the patients with PsO alone, the patients with combined PsO and gout had a significantly higher risk of CVD (relative risk 2.39, 95% CI 1.56 to 3.65). After adjustment for traditional risk factors, the risk of CVD was higher in patients with gout alone (HR 2.16, 95% CI 1.54 to 3.04) and in patients with combined PsO and gout (HR 2.72, 95% CI 1.73 to 4.28). Conclusions: Gout augments the risk of CVD independently of traditional risk factors in patients with PsO.